Answer :

We have,

…(i)


ax – by = 2ab …(ii)


By simplifying, we get


From equation (i),


…(iii)


From equation (ii),


ax – by – 2ab = 0 …(iv)


From equation (iii), we get a1 = a/b, b1 = - b/a and c1 = - (a + b)


And from equation (iv), we get a2 = a, b2 = - b and c2 = - 2ab


Using cross multiplication,







and


and


x = b and y = - a


Thus, x = b, y = - a


Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses
RELATED QUESTIONS :

Solve each of theRS Aggarwal - Mathematics

If 2x – 3y = 7 anRD Sharma - Mathematics

Solve the followiRD Sharma - Mathematics

Solve each of theRD Sharma - Mathematics